Comparison of Methods for Evaluating Mineral Loss: Hardness versus Synchrotron Microcomputed Tomography - Delbem, Alberto Carlos Botazzo [UNESP]; Sassaki, K. T.; Vieira, A. E. M.; Rodrigues, E.; Bergamaschi, M.; Stock, S. R.; Cannon, M. L.; Xiao, X.; De Carlo, F.; Delbem, Alberto Carlos Botazzo [UNESP] (Karger, 2009)
This study analyzed degrees of demineralization in bovine enamel using synchrotron microcomputed tomography (SMCT) and hardness measurements (Knoop hardness number, KHN). For 5 days, 40 bovine enamel blocks were individually subjected to a pH cycling model and treatment with fluoride dentifrices (placebo, 275, 550 and 1,100 mu g F/g) diluted in deionized water twice a day. Surface hardness number and cross-sectional profiles of hardness and mineral concentration (by SMCT) were determined. Integrated hardness (KHN x mu m) for sound and demineralized specimens was calculated and subtracted to give the integrated loss of hardness (Delta KHN) for the lesions. Increasing fluoride concentration in the dentifrices led to higher values for surface hardness after pH cycling and mineral concentration (g(HAp) cm(-3)), and lower values for Delta KHN (p < 0.05). From the present results, it may be concluded that hardness measurements revealed demineralization in all groups, which was lower in groups treated with dentifrice with a higher F concentration. SMCT and hardness measurements gave similar results in areas with higher demineralization, but diverged in areas with lower demineralization. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Bovine enamel; Hardness; In vitro; Synchrotron microcomputed tomography